Head and neck squamous cell carcinoma drives long interspersed element_1 hypomethylation in the peripheral blood mononuclear cells - Areeya Arayataweegool; Ratakorn Srisuttee; Patnarin Mahattanasakul; Napadon Tangjaturonsasme; Virachai Kerekhanjanarong; Nakarin Kitkumthorn; Apiwat Mutirangura (My University, 2018)
Alteration of long interspersed element-1 (LINE-1) methylation in peripheral blood mononuclear cells (PBMCs) has been simultaneously activated to breast carcinogenesis due to its secretion. To evaluate the effect in head and neck squamous cell carcinoma (HNSCC), LINE-1 methylation levels and patterns have been measured both in vitro and in vivo.Analysis of LINE-1 methylation in cocultured models between HNSCC cell lines and normal PBMCs was performed. The observation of PBMCs of HNSCC patients compared to PBMCs of normal controls was performed using the semiquantitative combined bisulfite restriction analysis technique.Downregulation of LINE-1 methylation was significantly found in the PBMCs cocultured with all HNSCC cell lines compared to normal PBMCs. Likewise, a reduction in LINE-1 methylation levels was observed in PBMCs of HNSCC compared to normal PBMCs (p < 0.0001). Receiver operating characteristic analysis demonstrated the potential of the unmethylated alleles (u Cu C) of LINE-1 for distinguishing the PBMCs of HNSCC patients from normal controls with 100% sensitivity and specificity.Our data supported that the alteration of LINE-1 methylation levels in PBMCs was influenced by HNSCC secretions. Moreover, the unmethylated LINE-1 allele of PBMCs was proved to be an effective tumor marker and possesses a potential as HNSCC diagnostic tool.
Keywords: Immunotherapy and Immune Responses